Advanced degradation of brominated epoxy resin and simultaneous transformation of glass fiber from waste printed circuit boards by improved supercritical water oxidation processes. (October 2016) - Liu, Kang; Zhang, Zhiyuan; Zhang, Fu-Shen
Highlights: An efficient approach for the recycle of waste PCBs by H2 O2 /NaOH improved SCWO systems was proposed. Waste PCBs were degraded into useful products and transformed into functional materials. Brominated epoxy resin was degraded into Cn H2n+2, CO2, H2 O and NaBr. Glass fiber was converted into anorthite and albite due to the alkali-silica reaction. The reaction mechanisms of H2 O2 /NaOH improved SCWO system were thoroughly elucidated. Abstract: This work investigated various supercritical water oxidation (SCWO) systems, i.e. SCWO1 (only water), SCWO2 (water + H2 O2 ) and SCWO3 (water + H2 O2 /NaOH), for waste printed circuit boards (PCBs) detoxification and recycling. Response surface methodology (RSM) was applied to optimize the operating conditions of the optimal SCWO3 systems. The optimal reaction conditions for debromination were found to be the NaOH of 0.21 g, the H2 O2 volume of 9.04 mL, the time of 39.7 min, maximum debromination efficiency of 95.14%. Variance analysis indicated that the factors influencing debromination efficiency was in the sequence of NaOH > H2 O2 > time. Mechanism studies indicated that the dissociated ions from NaOH in supercritical water promoted the debromination of brominated epoxy resins (BERs) through an elimination reaction and nucleophilic substitution. HO2, produced by H2 O2 could induce the oxidation of phenol ring to open (intermediates of BERs), which were thoroughly degraded to form hydrocarbons, CO2, H2 O and NaBr. In addition, the alkali-silica reaction between OH − and SiO2 induced the phase transformation of glass fibers, which were simultaneously converted into anorthite and albite. Waste PCBs in H2 O2 /NaOH improved SCWO system were fully degraded into useful products and simultaneously transformed into functional materials. These findings are helpful for efficient recycling of waste PCBs.